Theroleofinnovation in the relationship between university–industry collaboration in R&DandISO9001 - Aldabbas, Hazem (2020)
Purpose–Thisstudyaimstoinvestigatetherelationship between university–industry collaboration(U-I-C) in research anddevelopment (R&D)andqualitymanagement andexplorehowtherelationship ismediated by innovation. Design/methodology/approach– Basedonpanel data consisting of 109 countries spanning over a five year period (2013-2017) this study investigates, through structural equation modelling, how this relationship is mediated byinnovation. Findings– The main finding is that there are positive significant direct effects between U-I-C and innovation and between innovation and international organization for standardization (ISO) 9001. Furthermore, the strength and significance of these relations are highly affected by the classification of income in these countries, which ranges from high and upper-middle to lower-middle categories. This paper concludes that countries in the high-income category have higher achievement in U-I-C in R&D, innovation andISO9001whencomparedtotheupperandlower-middle-incomecategories. Originality/value– This paper demonstrates in the empirical study the value of collaboration in R&D between government, industry and academia, as it can encourage scientific research and contribute to quality management and innovation. This research is one of the very few studies to assess the country’s income classification effect on U-I-C in R&D, innovation and ISO 9001. It is recommended that more research is conducted on how countries not ranked in the high-income category could benefit from U-I-C in R&D to enhance innovationandquality management.